Strategi Dakwah Adenan bin Mohammad Aris dalam Meningkatkan Kesadaran Beragama Warga Binaan di Lapas Kelas IIA Bukittinggi - Balqis Khairunnisa; Darul Ilmi (Lembaga Yasin AlSys, 2026)
Although da‘wah strategies in inmate rehabilitation have received attention in various studies, research that specifically discusses the role of correctional inmates as da‘wah actors in increasing religious awareness in correctional institutions remains limited. This study aims to analyze the da‘wah strategy carried out by Adenan bin Mohamad Aris in guiding inmates to increase religious awareness at the Class IIA Bukittinggi Correctional Facility and to identify the obstacles and supporting factors in its implementation. This study used a qualitative approach with a case study design. The research participants consisted of correctional inmates and correctional facility officers selected using purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analyzed using descriptive qualitative analysis techniques through the stages of data reduction, data display, and conclusion drawing. The results showed that the da‘wah strategy implemented was structured, contextual, and adaptive to the psychological conditions and social backgrounds of the inmates. The dominant da‘wah method used was bil hikmah, an approach that emphasizes wisdom, persuasion, and empathy. The rehabilitation activities included Qur’an teaching, prayer guidance, and the delivery of basic religious materials. The findings also showed an increase in religious awareness, reflected in improved religious knowledge, worship practices, and behavioral change, although it was not yet fully permanent. The conclusion of this study confirms that contextual da‘wah strategies based on the bil hikmah approach play an important role in inmate rehabilitation. Its practical implication is that correctional institutions need to design religious rehabilitation programs that are more structured, empathetic, and sustainable to support behavioral change among correctional inmates.